A Systematic Literature Review of Investor Financial Behavior: Determinants, Biases, and Decision-Making Patterns - Idris, Hariany (Golden Ratio of Data in Summary, 2025)
This study presents a systematic literature review of 65 peer-reviewed publications from 2015 to 2025 examining investor financial behavior within the framework of behavioral finance. The review identifies key determinants such as cognitive and emotional biases (overconfidence, loss aversion, herding), socio-demographic factors (age, gender, education, and income), and the growing impact of digitalization and FinTech on investment decisions. Findings reveal that investors often deviate from rational models, with decision-making heavily influenced by psychology, information overload, and social pressure. In addition, the integration of Islamic ethical values provides a stabilizing moral framework that promotes responsible and sustainable investment. The study concludes that investor behavior is multidimensional shaped by the interaction between human cognition, culture, and moral principles. The review recommends enhancing financial literacy, developing ethical digital investment platforms, and incorporating behavioral insights into financial education and policy design to foster rational and value-driven financial ecosystems.